Impact of Malocclusion on Quality of Life in Sudanese Dental Students (Orthodontic Journal of Nepal, 2015)
Introduction: Both psychological and social factors come to play when analyzing oral health-related quality of life, and recent developments have shown that more focus has been placed on patients’ own perceptions of oral health status and oral health care systems to understand their needs, fulfillment with treatment, and ultimately the perceived overall quality of health systems.Objective: To assess the impact of orthodontic treatment needs on oral health-related quality of life of dental students.Materials & Method: A cross-sectional study was done on a random sample of 100 dental students aged 17-23 years at the University of Medical Sciences & Technology in Sudan. Each subject was assessed for orthodontic treatment need using Dental Health Component (DHC) of Index of Orthodontic Treatment Needs (IOTN). Each subject was given an Oral health-related quality to life questionnaire to complete the Oral Health Impact Profile (OHIP).Result: The oral health-related quality of life was generally good. Those with ‘definite need for treatment’ showed higher impact on oral health in relation to functional limitation and physical pain, than those who had ‘borderline need’, ‘little need’, or ‘no need for treatment’. Males with ‘borderline’ and ‘definite need for treatment’ generally showed higher impact on oral health than the female counterpart. However, this was not statistically significant. Conclusion: Malocclusion does not seem to affect the oral health-related quality of life to a significant degree.